Understanding sex differences in affective touch: sensory pleasantness, social comfort, and precursive experiences - Schirmer, Annett (2023)
Although previous research revealed sex differences in affective touch, the implicated processes and the manner in which men and women differ have been left uncertain. Here we addressed this issue in two studies examining sensory pleasure, interpersonal comfort, and touch motivators. Study 1 comprised a series of lab-based experiments in which a robot stroked 214 participants (half female) at five different velocities modulating the activity of C-tactile afferents thought to support tactile pleasantness. Average pleasantness ratings followed velocity with the typical inverted u-shape similarly in both sexes. In Study 2, 260 participants (half female) completed an online survey. Here, women were more likely than men to express touch comfort with less familiar or unknown individuals, had a greater preference for touch with other women, and felt more comfortable giving and receiving touch to the forearm. Additionally, when describing how their own experiences might motivate others to touch them affectively, women produced more negative descriptions than men. Together, these results show that, while the sexes compare in a touch's sensory pleasantness, they differ in their preceding affective experiences and how they value touch at a higher-order social level. This agrees with extant research on negative affect and stress and suggests that affective touch may be a more relevant coping mechanism for women than for men.